The Role of Fiqh Principles in Resolving Contemporary Family Issues - Samsul Arifin (UIN Mahmud Yunus Batusangkar, 2026)
This article examines the role of fiqh principles in addressing contemporary family issues arising from globalization, technological development, and changing social dynamics that increasingly challenge the realization of a sakinah, mawaddah, wa rahmah family. Using a qualitative approach with a literature study design, the research analyzes primary sources, including Ihya’ Ulumiddin and Al-Faraidul Bahiyyah, supported by books, journal articles, and other scholarly works on Islamic family law. Data were collected through library research and analyzed descriptively to identify the application of relevant fiqh principles to contemporary family disputes. The findings reveal three principal fiqh maxims that provide a methodological framework for judicial decision-making. First, la darara wa la dirara justifies divorce in cases of domestic violence to eliminate harm. Second, al-mashaqqah tajlib al-taysir enables judges to prioritize children's welfare by allowing flexibility in child custody decisions when strict legal rules create hardship. Third, dar’u al-mafasid muqaddam ‘ala jalb al-masalih guides judges in balancing competing interests in marriage dispensation cases by prioritizing the prevention of greater harm over the attainment of potential benefits. These principles demonstrate that fiqh maxims remain relevant as adaptive legal instruments for resolving contemporary family issues while preserving the objectives of Islamic law.